Efficacy and safety of 400 mg efavirenz versus standard 600 mg dose when taken with tenofovir and lamivudine combination in Indian adult patients with HIV-1 infection: An open-label, interventional, randomized, non-inferiority trial. Issue 48 (2nd December 2022) - Dravid, Ameet; Pilawan, Anant S.; S., Anuradha; Morkar, Dnyanesh N.; Ramapuram, John T; Madhukarrao, Kulkarni Milind; Naik, K. Sunil; Bhrusundi, Milind; K. R, Raveendra; Nageswaramma, Siddabathuni; Kulkarni, Vinay
Abstract : Background: To evaluate the non-inferiority of low dose efavirenz (400 mg) to standard dose efavirenz (600 mg), when taken in combination with tenofovir and lamivudine in Indian patients with HIV-1 infection. Methods: An open-label, interventional phase IV study with blinded assessment was conducted across 17 sites in India. HIV-1-infected antiretroviral therapy-naive adult patients (≥18 years of age) with a plasma HIV-1 viral load of at least 1000 copies per mL were randomized to receive either tenofovir/lamivudine/efavirenz (TLE) 400 or TLE 600. The primary endpoint was the difference in the proportion of patients achieving < 200 copies per mL at the end of 24 weeks. Results: A total of 265 patients were enrolled and were randomized in 1:1 ratio to TLE 400 group (130 patients) and TLE 600 group (135 patients). At week 24, the proportion of patients with a viral load of less than 200 copies per mL was 80.70% for TLE 400 and 78.95% for TLE 600 (difference 1.75%, 90% confidence interval: −7.01, 10.49) which was within the predefined margin of −10% (90% confidence interval). Significantly lower study drug-related adverse events were observed in TLE 400 group compared to TLE 600 group (52.30%, n = 68 vs 64.92%, n = 87; P  = .037). The treatment discontinuation percentage was marginally higher by 2.08% in TLE 600 group. Conclusion: The fixed-dose combination of TLE 400 is non-inferior to TLE 600 in terms of viral suppression and has an improved safety profile over 24 weeks in adult Indian patients with HIV-1 infection.